Aflatoxin in Aegle marmelos (Linn.) Correa Ex Roxb - Singh, Punam Kumari; Harsh, N. S. K. (Indian Forester, 2002)
Aegle marmelos fruits are widely used in preparation of indigenous/ayurvedic medicines and different edible products. The fruits collected from different pharmaceutical industries during summer, monsoon and winter seasons were analysed for fungal association and aflatoxin contamination. Nine fungi comprising Alternaria alternata, Actinomucor repens, Aspergillus flavus, A. niger, A. ochraceus, Fusarium verticillioides, F. solani, Penicillium citrinum and Rhizopus stolonifer were recorded. The frequency of mycotoxigenic fungi A. flavus, A. ochraceus and P. citrinum was high in the stored fruits of A. marmelos. Thirty six percent of the isolates of A. flavus were found to be toxigenic and the level of aflatoxin B1 ranged from 0.9 . 26.0 Î¼g/ml. The concentration of aflatoxin B1 as natural contaminant was as high as 1.09 Î¼g/g. The concentration of aflatoxin B1 was fairly high in samples of all sources during monsoon. The study demonstrates that A. marmelos fruits are very prone to aflatoxin contamination. There is a need to analyse the samples for their aflatoxin levcl before being consumed or marketed for preparation of indigenous medicines and other edible products.